Characterization of the SPI‐1 and Rsp type three secretion systems in Pseudomonas fluorescens F113. Issue 3 (25th February 2013) - Barret, Matthieu; Egan, Frank; Moynihan, Jennifer; Morrissey, John P.; Lesouhaitier, Olivier; O'Gara, Fergal
Summary Pseudomonas fluorescens F113 is a plant growth‐promoting rhizobacterium (PGPR) isolated from the sugar beet rhizosphere. The recent annotation of the F113 genome sequence has revealed that this strain encodes a wide array of secretion systems, including two complete type three secretion systems (T3SSs) belonging to the Hrp1 and SPI‐1 families. While Hrp1 T3SSs are frequently encoded in other P. fluorescens strains, the presence of a SPI‐1 T3SS in a plant‐beneficial bacterial strain was unexpected. In this work, the genetic organization and expression of these two T3SS loci have been analysed by a combination of transcriptional reporter fusions and transcriptome analyses. Overexpression of two transcriptional activators has shown a number of genes encoding putative T3 effectors. In addition, the influence of these two T3SSs during the interaction of P. fluorescens F113 with some bacterial predators was also assessed. Our data revealed that the transcriptional activator hilA is induced by amoeba and that the SPI‐1 T3SS could potentially be involved in resistance to amoeboid grazing.